Diseño de la Estructura Organizacional y Funcional para la Cooperativa de Producción y Comercialización Agropecuaria “AGROBALSAS”, del Cantón Marcabelí. - Reyes Sánchez, María Rosa (2024)
This research focuses on the elaboration of the design of the organic and functional structure for the Cooperative “AGROBALSAS”, since this aspect influences the efficiency, adaptability and responsiveness to challenges that arise in their environment, taking into account these aspects, it was decided to use techniques and instruments that served for the collection of information, The information was used to carry out a situational diagnosis where weaknesses were identified, such as the lack of well- structured organizational charts, the absence of a welcome manual and a procedures manual, so a structural organizational chart was drawn up to graphically represent the hierarchical levels, as well as a functional organizational chart to define each of the functions of each position, avoiding duplication of functions within the cooperative. A welcome manual was prepared containing the company's business philosophy, organizational charts and location of the company. This document provides an overview of the cooperative's organizational culture. The development of the procedure’s manual was focused on two main procedures, which are the production and sale of balanced products. As for the methodology used, it was a qualitative approach, accompanied by an inductive method through the application of techniques such as the survey and the interview, which were used for data collection. Regarding the conclusions, it can be highlighted that the proposed objectives were achieved, which were based on a situational diagnosis and a proposal for an organizational design. Finally, in relation to the recommendation, the cooperative should review the proposal in order to be able to implement it.